PTU-049 Rate of disease progression and the influence of co-factors in hepatitis C virus as determined by interval liver biopsy. (23rd September 2015) - Abbara, A; Kennedy, P; Gordon, F; Brown, A; Goldin, R; Main, J; Thomas, H; Thursz, M
Abstract : Introduction: Treatment candidates for emerging small molecule therapy in hepatitis C virus (HCV) have yet to be defined. Treatment naive patients who have opted to delay standard of care therapy will compete with treatment failures for these novel agents. For this reason, disease progression needs to be clearly defined. While the role of liver biopsy in the management of HCV remains contentious, data on the progression of fibrosis can only be ascertained from sequential liver biopsy. Thus, patients in our unit who underwent interval biopsies were studied to identify the factors which determine disease progression. Methods: A total of 242 mono-infected HCV patients underwent a repeat liver biopsy. Patients who declined treatment and opted for a strategy of watchful waiting and those who failed combination antiviral therapy were offered an interval biopsy. Demographic data, viral parameters, ALT level, necro-inflammatory (NI) score and the presence of co-factors were collated to investigate their impact on progression of disease. Statistical analysis was performed using a Linear Mixed Model with SPSS 16 and the level of significance used was 5%. Results: 121/242 patients had evidence of disease progression on interval biopsy. The median interval between biopsies was 50 months (range 11–133). Age, ALT level and necro-inflammatory score were all predictors of progressive fibrosis, p<0.002, p<0.001, p<0.0001, respectively. The presence of a co-factor, defined as features of concurrent alcohol ingestion, steatosis or iron on liver biopsy lead to a doubling of the rate of fibrosis when compared with no co-factor. Neither genotype nor gender had a significant impact on fibrosis progression. Conclusion: Liver biopsy benchmarks the extent of fibrosis in chronic HCV infection. This is critical in determining treatment response; moreover it provides an insight into future disease progression in those who decline treatment. This study demonstrates age. ALT and NI score as factors associated with accelerated disease, while the presence of a co-factor can have a synergistic effect, doubling the rate of fibrosis progression in HCV infection.